2005
DOI: 10.1021/ic0482537
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(III) Carbonate and Bicarbonate Chelate Complexes of Tripodal Tetraamine Ligands Containing Pyridyl Donors:  The Steric Basis for the Stability of Chelated Bicarbonate Complexes

Abstract: The synthesis and characterization (X-ray crystallography, UV/vis spectroscopy, electrochemistry, ESI-MS, and (1)H, (13)C, and (59)Co NMR) of the complexes [Co(L)(O(2)CO)]ClO(4)xH(2)O (L = tpa (tpa = tris(2-pyridylmethyl)amine) (x = 1), pmea (pmea = bis((2-pyridyl)methyl)-2-((2-pyridyl)ethyl)amine) (x = 0), pmap (pmap = bis(2-(2-pyridyl)ethyl)(2-pyridylmethyl)amine) (x = 0), tepa (tepa = tris(2-(2-pyridyl)ethyl)amine) (x = 0)) which contain tripodal tetradentate pyridyl ligands and chelated carbonate ligands a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
5
15
0
Order By: Relevance
“…Below this temperature, the c M T value descends slowly to reach 1.10 cm 3 mol À1 K at 100 K, and then it remains fairly constant with decreasing temperature until 45 K. Further cooling to 15 K leads to the c M T value equal to 0.80 cm 3 mol À1 K. This weak paramagnetism can be related to a residual amount of the HS fraction A C H T U N G T R E N N U N G (%20 %), probably due to the slow kinetics of HS!LS relaxation. [19] In the warming mode the same magnetic behavior as in the cooling one was observed. Because of potentially explosive properties of the perchlorate salts, the complexes 2 c and 3 c were heated to 330 K. For compound 2 c, the variation of c M T in the range of 85-330 K conforms to a partial (55 %) spin conversion with T 1/2 equal to 320 K. The compound 3 c shows a weak increasing tendency for the c M T value up to 330 K, so the presence of spin crossover at higher temperatures can be expected.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Below this temperature, the c M T value descends slowly to reach 1.10 cm 3 mol À1 K at 100 K, and then it remains fairly constant with decreasing temperature until 45 K. Further cooling to 15 K leads to the c M T value equal to 0.80 cm 3 mol À1 K. This weak paramagnetism can be related to a residual amount of the HS fraction A C H T U N G T R E N N U N G (%20 %), probably due to the slow kinetics of HS!LS relaxation. [19] In the warming mode the same magnetic behavior as in the cooling one was observed. Because of potentially explosive properties of the perchlorate salts, the complexes 2 c and 3 c were heated to 330 K. For compound 2 c, the variation of c M T in the range of 85-330 K conforms to a partial (55 %) spin conversion with T 1/2 equal to 320 K. The compound 3 c shows a weak increasing tendency for the c M T value up to 330 K, so the presence of spin crossover at higher temperatures can be expected.…”
Section: Introductionsupporting
confidence: 57%
“…[19][20][21] Although, this feature concerns s-bonding, some effects from p-bonding also can not be excluded. The tilt of the pyridine rings, probably a result of packing effects, modifies the p-acceptor properties of the aromatic-nitrogen atoms.…”
Section: And Cobalta C H T U N G T R E N N U N G (Iii)mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the similar pK a values, 1 and 2 exhibit very different reactivity towards chelate ring opening, and this observation provides a possible explanation for the unusual stability of the chelated HPO 4 2À ligand in 1. We have previously shown that the structurally similar complexes [LCoA C H T U N G T R E N N U N G (O 2 CO)] + (L = tpa, Metpa, Me 2 tpa, Me 3 tpa, pmea, pmap, tepa) containing a chelated carbonate ligand [34][35][36] exhibit extraordinary stability toward acid hydrolysis in acidic aqueous solution owing to the fact that the tripodal ancillary ligands provide sufficient steric hindrance at the coordinated endo O atoms to inhibit protonation at these sites. This renders CoÀO bond cleavage and subsequent chelate ring-opening more difficult than in complexes such as [Co(en) 2 O 2 CO] + , which undergo rapid evolution of CO 2 in acidic aqueous solution.…”
mentioning
confidence: 99%
“…We are currently investigating the reactivity of 1 and the synthesis of related HPO 4 2À -containing complexes. [35] , the cation is fluxional at room temperature); 31 (2); Co1-O1, 1.916(2); Co1-N21, 1.922(2); Co1-O2, 1.928(2); Co1-N1, 1.943(2); Co1-N11, 1.945(2); P1-O3, 1.497(2); P1-O4, 1.553(2); P1-O1, 1.554(2); P1-O2, 1.555(2); O1-Co1-O2, 76.11 (8); O1-Co1-N1, 90.34(9); O2-Co1-N11, 94.71(8); N1-Co1-N11, 98.83(10); O3-P1-O4 110.27 (12); O1-P1-O2, 99.32 (10).…”
mentioning
confidence: 99%